Systematic Review of Escalated Imatinib Doses Compared with Sunitinib or Best Supportive Care, for the Treatment of People with Unresectable/Metastatic Gastrointestinal Stromal Tumours Whose Disease has Progressed on the Standard Imatinib Dose - Hislop, Jennifer (Springer US, 2011)
INTRODUCTION: We conducted a systematic review of evidence on the effectiveness of imatinib at escalated doses of 600 mg/day or 800 mg/day for treatment of adults with unresectable or metastatic gastrointestinal stromal tumours (GIST), following progression on imatinib at the 400 mg/day dose, compared with sunitinib and/or ‘best supportive care’. METHODS: Electronic searches were undertaken to identify relevant randomised controlled trials (RCTs), non-randomised studies, and case series reporting outcome data on survival, quality of life or adverse events. Titles and abstracts were screened by two reviewers and full text reports of potentially relevant studies assessed for inclusion. Included studies were quality assessed by two reviewers and data were extracted. Five studies reported data on the relevant population and were included. RESULTS AND DISCUSSION: Median overall survival for imatinib (800 mg/day) and sunitinib both were less than 2 years. Around 25% of patients required either an imatinib dose delay or reduction. Approximately one-third of patients receiving dose escalated imatinib (either dose) showed either response or stable disease. Amongst those responding to the escalated 800 mg/day dose, median progression-free survival was over 25 months. The statistical likelihood of response may depend on exon mutational status. There were few data and those that were available were potentially biased, due to their non-randomised nature. Further data are needed to justify international guideline recommendations on imatinib dose escalation. CONCLUSION: A prospective audit of management and outcomes for unresectable GIST patients treated with dose escalation upon progression at 400 mg/day may be appropriate as an RCT may be unfeasible.